Power and Resistance in the New World Order - Gill, S. author. aut Link
XXVI, 288 p.
Keywords: In this fully revised and updated new edition, leading political scientist Stephen Gill further develops his radical theory of the new world order to argue that as the globalization of power intensifies, so too do globalized forms of resistance. Including two new chapters, this widely adopted text offers alternatives to the current world order.